The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/07908318.2019.1571078
|View full text |Cite
|
Sign up to set email alerts
|

CLIL, an elitist language learning approach? A background analysis of English and Dutch CLIL pupils in French-speaking Belgium

Abstract: Content and language integrated learning (CLIL) programs are increasingly popular throughout Europe, but are sometimes accused of inducing a selection bias in the pupil population, both through selection mechanisms of the schools themselves and self-selection of the pupils (and/or their parents). As a result, the outcomes of the CLIL approach may be artificially promoted, and, at the same time, such a selection bias can contribute to an elitist education model, which arguably runs counter to the aims of the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In light of studies elsewhere that have raised, for example concerns regarding elitism, (e.g. (Bruton, 2011;2015); Van Mensel et al (2019)) this is interesting. Challenge to professional integrity (Moate, 2011) that can demotivate teacher practice was not evident in the findings.…”
Section: Constraintsmentioning
confidence: 94%
See 1 more Smart Citation
“…In light of studies elsewhere that have raised, for example concerns regarding elitism, (e.g. (Bruton, 2011;2015); Van Mensel et al (2019)) this is interesting. Challenge to professional integrity (Moate, 2011) that can demotivate teacher practice was not evident in the findings.…”
Section: Constraintsmentioning
confidence: 94%
“…Bruton 2011;2015) question the extent to which CLIL per se may be responsible for reported learner gains. Van Mensel et al (2019) for example found socio economic background to be a factor in CLIL enrolment and Paran (2013) questions the suitability of CLIL for learners of all abilities. Pérez Cañado (2019) recently challenges such concerns.…”
Section: Background the European Context And The Development Of Clil mentioning
confidence: 99%
“…In contrast to the English texts, the pupils' non-verbal intelligence also correlates with two of the outcome measures, namely word length and lexical diversity. This observation can be explained by the reported significant differences in Raven scores between the pupils in CLIL and non-CLIL contexts learning Dutch (Simonis et al, 2019;Van Mensel et al, 2019), differences that 6. We should, however, note that the p value of the correlation between word length and length of TL exposure is only just below the cut-off point of .05 (.048).…”
Section: Correlationsmentioning
confidence: 98%
“…The participants involved in this study were 412 1 5th year (Grade 11) Frenchspeaking secondary school learners of Dutch and English from nine secondary schools in Wallonia (French-speaking Belgium). The participating schools had contrasted profiles, notably in terms of location (all provinces are covered), socioeconomic level, and education authority (official education and publicly subsidized schools) (see also Hiligsmann et al, 2017;Van Mensel et al, 2019). These schools provided CLIL programs in Dutch and/or English, along with traditional instruction (French-medium instruction with foreign language classes).…”
Section: Participantsmentioning
confidence: 99%
“…CLIL programmes are an approach to learn English or another foreign language by combining language and content subjects. In some contexts, CLIL is selective and this selection can be based on cognitive abilities or may also be linked to socio-economic backgrounds ( Van Mensel et al, 2020). The integration of content and language is one of the main characteristics of the CLIL approach, as the relationship between these two elements is at the core of any implementation (Llinares & Morton, 2017;Nikula et al, 2016).…”
Section: The Clil Approachmentioning
confidence: 99%